Revolution of CAR Engineering For Next-Generation Immunotherapy In Solid Tumors - Yu, Tao; Yu, Shao-kun; Xiang, Yan; Lu, Kai-Hua; Sun, Ming (Frontiers in Immunology, 2022)
CAR-T cells have enormous potentials for clinical therapies. The CAR-T therapy has been approved for treating hematological malignancies. However, their application is limited in solid tumors owing to antigens loss and mutation, physical barriers, and immunosuppressive tumor microenvironment. To overcome challenges of CAR-T, surging efforts are put into developing CAR-T to increase its applied ranges. Varied receptors are utilized for recognizing tumor associated antigens and relieving immunosuppression. Emerging costimulatory signaling is employed for CAR-T activation. Besides, other immune cells such as NK cells and macrophages have manifested potential for delivering CAR. Hence, we collected and summarized last progresses of CAR engineering from three aspects, including the ectodomains, the endogenous domains, and immune cells, aiming to inspire designs of the next generation adoptive immunotherapy for treating solid tumors.